Expansion of Hair Follicle Stem Cells Sticking to Isolated Sebaceous Glands to Generate in Vivo Epidermal Structures - Huishan Zhang (Cell Transplantation, 2016)
Hair follicle stem cells (HFSCs) are considered one of the useful donor cell types for skin regenerative medicine owing to their robust proliferative capacity and multipotency. However, methods for easily and effectively obtaining HFSCs from a limited skin biopsy are still lacking. Here we report a novel approach for obtaining a subpopulation of HFSCs from a small skin sample from the rat tail, which uses the sebaceous glands (SGs) to capture the adjacent HFSCs. By means of organ culture, keratinocytes were expanded from the detached SGs, which also included adherent HFSCs from the hair follicle that could be passaged at the single-cell level. These SG-captured keratinocytes strongly expressed the basal layer markers K14, integrin α6, and p63; the bulge stem cell marker K15; and the upper isthmus stem cell marker Plet1. Furthermore, we reconstituted new epidermis, hair follicles, and SGs from the SG-captured keratinocytes using an easily operated, modified skin reconstitution assay based on silicone gel sheeting. This study suggests that the SGs could be an accessible capturer to harvest the adjacent HFSC subpopulation, particularly when the donor tissue is limited.